Presencia de Juana de Arco en Costa Rica - Le Franc Ureña, Roberto (2016)
Born in 1412 at Domrémy, France, Joan also know as "the maid of France", was ínspired by God to drive of the british who invaded France.Charles Dauphin of France gave her a little army, she laid siege and liberated the city of Orleáns in 1429 and brought Charles to Reims to be confirrned as a King Charles VII of France.Captured by the british army, she was tried as a wiích by an ecclesiastical court, and buraed to dead in Rouen in 1431.In 1909 pope Benedict XV beatified Joan and considered her a saint in 1920.In Costa Rica the history of Joan of Are was best know at the end of XIX century probably popularized by the sisters of Notre Dame of Sión. El objetivo de este ensayo será reconocer la presencia de la esta heroína en Costa Rica, a pesar de ser una figura tan ajena a la realidad nacional.